A Study on Morphometric and Meristic of Helostoma temmincki from swamp area in the Bencah Kelubi Village, Tapung Kiri Sub-Regency, Kampar Regency, Riau Province - Muryati, Siti; Putra, Ridwan Manda; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Helostoma temmincki is a type of fish that inhabit swamp area in the Bencah Kelubi Village. This fish has high economical value, around Rp 25,000-30,000/Kg. Information on biological aspects of this fish, including morphometric and meristic and is rare. To understand the morphometrical, meristical characteristics and growth pattern of this fish, a research had been conducted from June to August 2015. There were 141 fishes (60-121 mm SL and 10.18-87.56 gr BW) captured from the swamp area in the Bencah Kelubi Village. There were 26 morphological characteristics measured and 6 meristical characteristics studied. Results shown that all of morphometrical characteristics were almost isometric as the fish growing. The meristical characteristic of the fish were as follow: D.XVI-XVIII.13-16; A.XIII-XV.17-19; P.10-11; C. 13-16 and lateral line scale was 44-48. All of morphological characteristics measured were then compared with SL to understand the growth pattern. The Lenght-Weight relationship shown that the growth of male and female H. temmincki was isometric. The water quality parameter shown that temperature 28-31°C, transparency 17-46.5 cm, pH 5-6, DO 2-3.8 mg/L and CO2 14-20 mg/L. Data on water quality parameters indicate that water quality from the swamp area in the Bencah Kelubi Village is able to support the life of the H. temmincki.Keywords : Helostoma temmincki, swamp, morphometric, meristic, growth patterns